2005
DOI: 10.1007/s00526-005-0327-8
|View full text |Cite
|
Sign up to set email alerts
|

C1,α-solutions to non-autonomous anisotropic variational problems

Abstract: We establish several smoothness results for local minimizers of nonautonomous variational integrals with anisotropic growth conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 22 publications
2
55
0
Order By: Relevance
“…From [LU] (see the discussion in Remark 2.3 of [BF4]) we deduce that u δ is in the space W 2 t,loc (B R (x 0 )) for any t < ∞, therefore we may test the differentiated Euler equation valid for u δ with the function η 2 ∂ γ u δ Γ β/2 δ , where β ≥ 0, η ∈ C ∞ 0 (B R (x 0 )) and γ runs from 1 to n − 1. Since we consider the scalar case, it is easy to check that (from now on summation w.r.t.…”
Section: This Givesmentioning
confidence: 99%
See 3 more Smart Citations
“…From [LU] (see the discussion in Remark 2.3 of [BF4]) we deduce that u δ is in the space W 2 t,loc (B R (x 0 )) for any t < ∞, therefore we may test the differentiated Euler equation valid for u δ with the function η 2 ∂ γ u δ Γ β/2 δ , where β ≥ 0, η ∈ C ∞ 0 (B R (x 0 )) and γ runs from 1 to n − 1. Since we consider the scalar case, it is easy to check that (from now on summation w.r.t.…”
Section: This Givesmentioning
confidence: 99%
“…Having established (4.8), the proof of C 1,α -regularity can be obtained following for example [Bi], proof of Theorem 5.22, or [BF4] Lemma 2.9, where it is shown that from (4.8) we can deduce ∇u δ L ∞ (Bρ(x 0 )) ≤ c(ρ) < ∞. Uniform Hölder continuity of ∇u δ then follows as outlined in [BF4], end of Section 2.1.…”
Section: Thus (Using (42))mentioning
confidence: 99%
See 2 more Smart Citations
“…The regularity for variational problems and differential equations with nonstandard growth has been studied extensively and many interesting results have been obtained, for example, we refer to [8,12,34] for general (p, q) growth case, refer to [1,[4][5][6][19][20][21][30][31][32][33] for − → p growth case and refer to [2,9,10,[13][14][15][16][17]25,41,44,45] for p(x) growth case. To our knowledge, the regularity for the − → p (x) growth case has not yet been studied specially and systematically.…”
Section: Fan Nodeamentioning
confidence: 99%